Long-term durability of bioprosthetic aortic valve replacement in young patients with bicuspid aortic stenosisCentral MessagePerspective - Christopher K. Mehta, MD; Tom X. Liu, MD, MS; Abigail S. Baldridge, DrPh; Jane Kruse, BSN; Jyothy Puthumana, MD; Robert O. Bonow, MD; Duc T. Pham, MD; Douglas R. Johnston, MD; S. Christopher Malaisrie, MD; Patrick M. McCarthy, MD (JTCVS Structural and Endovascular)
Objective: To examine long-term surgical aortic valve replacement (SAVR) outcomes for young (ie, younger than age 65 years) patients with bicuspid aortic valve and aortic stenosis (AS) with or without concomitant aneurysm. Background: There are few studies evaluating the early and late outcomes of SAVR in young patients (younger than age 65 years) with bicuspid aortic valve and AS. Methods: Using institutional data from 2004 through 2022, 498 patients with bicuspid aortic valve younger than age 65 years underwent SAVR for AS with bioprosthetic valves. We examined operative outcomes, long-term valve durability, and reintervention. Results: The total cohort comprised 281 patients undergoing isolated SAVR and 217 with concomitant aneurysm repair (SAVR/aneurysm). The average age was 55 ± 8 years, with Society of Thoracic Surgeons predicted risk of mortality score of median 0.7 (IQR 0.5, 1.0) and mean valve size of 25 mm. Operative mortality (0.7% vs 1.4%; P = .77) was similar between SAVR and SAVR/aneurysm patients. Predischarge permanent pacemaker implantation occurred in 1.6% (8 out of 498) patients. During overall follow-up of 5.0 years (IQR 1.8-9.9; range, 0.2-18.2 years), the cumulative incidence of reintervention at 10 years for structural valve degeneration (n = 33), including valve-in-valve (n = 15) was 6.6% (8.1% SAVR vs 4.5% SAVR/aneurysm; P = .66). No mortality was observed for valve-in-valve or redo-SAVR. Moderate or greater aortic regurgitation and paravalvular leak were observed in 6.5% and 0.3%, respectively, at most recent follow-up. Conclusions: Bicuspid AS is common in patients younger than 65 years and management includes consideration of future valve intervention. SAVR confers excellent operative and reoperative outcomes, 10-year durability, and valve function. These results may support initial SAVR when considering lifetime management of AS.